Prevalence and factors associated with depression symptoms among school-going adolescents in Central Uganda - Joyce Nalugya; Godfrey Zari Rukundo; Emilio Ovuga; Steven M. Kiwuwa; Seggane Musisi; Etheldreda Nakimuli‐Mpungu (2016)
Depression in adolescents constitutes a global public health concern. However, data on its prevalence and associated factors are limited in low income countries like Uganda. Using a cross-sectional descriptive study design, 519 adolescent students in 4 secondary schools in Mukono district, Uganda, were randomly selected after meeting study criteria. The 4 school types were: boarding mixed (boys and girls) school; day mixed school; girls' only boarding school; and, boys' only boarding school. The 519 participants filled out standardized questionnaires regarding their socio-demographic characteristics and health history. They were then screened for depression using the Children Depression Inventory (CDI) and those with a cut-off of 19 were administered the Mini International Neuro-Psychiatric Interview for Children and Adolescents 2.0 (MINI-KID), to ascertain the Diagnostic and Statistical Manual of Mental Disorders, 4th Edition (DSM IV) diagnostic types of depression and any co morbidity. Logistic regression analyses were used to assess factors associated with significant depression symptoms (a score of 19 or more on the CDI). There were 301 (58 %) boys and 218 (42 %) girls with age range 14–16 years and a mean age of 16 years (SD 2.18). Of 519 participants screened with the CDI, 109 (21 %) had significant depression symptoms. Of the 109 participants with significant depression symptoms, only 74 were evaluated with the MINI-KID and of these, 8 (11 %) met criteria for major depression and 6 (8 %) met criteria for dysthymia. Therefore, among participants that were assessed with both the CDI and the MINI-KID (n = 484), the prevalence of depressive disorders was 2.9 %. In this sample, 15 (3.1 %) reported current suicidal ideation. In the logistic regression analyses, significant depression symptoms were associated with single-sex schools, loss of parents and alcohol consumption. This is a cross-sectional study therefore, causal relationships are difficult to establish. Limited resources and the lack of collateral information precluded the assessment of a number of potential factors that could be associated with adolescent depression. The MINI-KID was administered to only 74 out of 109 students who scored ≥19 on the CDI since 35 students could not be traced again due to limited resources at the time. Significant depression symptoms are prevalent among school-going adolescents and may progress to full-blown depressive disorders. Culturally sensitive psychological interventions to prevent and treat depression among school-going adolescents are urgently needed.